Effectiveness of an 8-week Digital Prevention Course with Exergames on Physical Activity and Stress Management in University Students in Germany - Alina Bart (2025)
Background: Different health parameters within the population of university students in Germany had a negative trend in the recent years. University students tend to have low physical activity (PA) levels and high stress levels (SL), which can lead to poor health and low (subjective) well-being (SWB). The promotion of PA shows promising results in improving those parameters. Exergames have recently gained attention in the use of health contexts, by promoting PA in a motivating and enjoyable way. The ergofox GmbH has developed a digital prevention course with Exergames, with the aim to promote PA, reduce SL and enhance SWB in university students. Methods: The digital prevention course with Exergames had a duration of eight weeks with one course unit per week. Digital pre- and post-questionnaires were implemented to assess the effectiveness on PA, SL and SWB and the feasibility. Dependent t-tests and Wilcoxon signed-rank tests were used to assess significant differences in the pre- and post-intervention variables among the participants. Bivariate analyses in form of Spearman correlation analyses and point-biserial analyses were used to assess significant correlations of the variables with the course participation. The feasibility and suitability of the measure was assessed with descriptive analyses and thematic analyses for the open-ended questions. Results: Despite the fact that the participants who participated regularly in the course (n = 24) showed significant improvements in PA (z = 2.31; p = 0.021; r = 0.33), SL (z = -2.99; p = 0.003; r = 0.43) and SWB (t (23) = 5.47; p < 0.001; r = 0.75) after the intervention phase, it is not possible to attribute these improvements to the digital prevention course. No significant correlation was found between the changes in the variables and the course participation. The improvements might have been caused by confounding variables. The analysis of the data on feasibility and suitability as health promotion measure showed mostly positive ratings, however, participants indicated technical issues and a lack of intensity. Conclusion: The digital prevention course with Exergames was found to not be effective in improving PA, reducing SL and enhancing SWB among university students. However, the participants rated it to be a feasible and suitable health promotion measure, which still needs improvements. Further comprehensive research with a larger sample size and an enhanced research design is needed to gain further insights into this topic.
Keywords: University students; Exergames; Physical activity; Stress level; Subjective well-being; Health promotion